2022
DOI: 10.1038/s41467-022-34752-1
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the catalytically active APOBEC3G bound to a DNA oligonucleotide inhibitor reveals tetrahedral geometry of the transition state

Abstract: APOBEC3 proteins (A3s) are enzymes that catalyze the deamination of cytidine to uridine in single-stranded DNA (ssDNA) substrates, thus playing a key role in innate antiviral immunity. However, the APOBEC3 family has also been linked to many mutational signatures in cancer cells, which has led to an intense interest to develop inhibitors of A3’s catalytic activity as therapeutics as well as tools to study A3’s biochemistry, structure, and cellular function. Recent studies have shown that ssDNA containing 2′-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 80 publications
4
8
0
Order By: Relevance
“…1g ). This, together with prior work indicating hydration of dZ and its derivatives in structures with CDA, A3A 19-20 and A3G 38-40 , demonstrate a universal mechanism of inhibition 18-19, 38-40 .…”
Section: Resultssupporting
confidence: 67%
“…1g ). This, together with prior work indicating hydration of dZ and its derivatives in structures with CDA, A3A 19-20 and A3G 38-40 , demonstrate a universal mechanism of inhibition 18-19, 38-40 .…”
Section: Resultssupporting
confidence: 67%
“…Very recently, using X-ray crystallography it was revealed that FdZ and dZ form tetrahedral intermediates (4-( R )-hydroxy-3,4-dihydro-2′-deoxy-5-fluorozebularine and 4-( R )-hydroxy-3,4-dihydro-2′-deoxyzebularine) in the enzyme's active site with wild-type A3A 42,43 and catalytically active C-terminal domain of A3G. 59 The position of OH in hydrated FdZ and dZ is the same in the complex with CDA and A3 with carbon C4 having R -stereochemistry. Considering that the nomenclature changes when we replace N3 in 1,3-diazepin-2-one to CH 2 in azepin-2-one (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We also demonstrated that IIc-and IId-containing DNAs also inhibit fulllength wild-type A3G with similar efficiency to that for the single catalytically active CTD [57,58]. Recently, analysis of crystal structures revealed that both dZ (IIc) and FdZ (IId) form tetrahedral intermediates after hydrolysis of the N3-C4 double bond in the active sites of A3Gctd and A3A [59,60]. The intermediates formed had the same R-stereochemistry at the C4 atom of the nucleobase as previously observed for CDA, and thus confirming the general mechanism of cytosine deamination for A3 and CDA [50,[59][60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 75%
“…Nucleoside and polynucleotide (A3) CDA share a universal mechanism of target nucleobase engagement, deamination and inhibition [50,[59][60][61][62][63][64]. We have recently demonstrated the first inhibition of A3A-induced mutagenesis in cells using a DNA hairpin carrying FdZ (IId) instead of the target C in the TTC loop [60].…”
Section: Discussionmentioning
confidence: 99%